Biomarkers of liver fibrosis - Morling, Joanne R.; Guha, Indra Neil (Wiley, 2016)
Currently the only accepted method (gold standard) for the diagnosis of the fibrotic stages of chronic liver disease (CLD) is liver biopsy, to allow histological assessment. Liver biopsy is an invasive investigation associated with a range adverse events (e.g. pain, haemorrhage) limiting its serial usage in clinical practice. Additionally, its use is further reduced by sampling error and because histology is in effect a surrogate for clinical outcomes. Over recent years, alternative non-invasive biomarkers for the diagnosis of liver fibrosis have been developed. Initially developed in chronic viral hepatitis these have since seen their use expanded to include all aetiologies of CLD. Such markers can be divided into indirect ‘simple’ markers (e.g. transaminases, gamma-glutamyl transferase, platelet count), direct ‘complex’ markers (e.g. procollagen peptides I/III, Type IV collagen), cytokines (e.g. interleukin-10, transforming growth factor alpha) and imaging. Here, we discuss the clinical utility, limitations and development of non-invasive biomarkers in their use as diagnostic and prognostic tests.